Host-Specific and Environment-Dependent Effects of Endophyte Alternaria oxytropis on Three Locoweed Oxytropis Species in China - Yue-Yang Zhang; Yan-Zhong Li; Zun-Ji Shi (Journal of Fungi)
Plant–endophyte symbioses are widespread in grasslands. While symbiotic interactions often provide hosts with major fitness enhancements, the role of the endophyte Alternaria oxytropis, which produces swainsonine in locoweeds (Oxytropis and Astragalus spp.), remains enigmatic. We compared endophyte-infected (E+) and endophyte-free (E−) plants of three main Chinese locoweed species (O. kansuensis, O. glabra, and O. ochrocephala) under controlled conditions, and analyzed environmental factors at locoweed poisoning hotspots for herbivores. The results demonstrated significant species-specific effects: E+ plants of O. glabra and O. ochrocephala exhibited 26–39% reductions in biomass, net photosynthetic rate, and stomatal conductance, with elevated CO2 levels, while O. kansuensis showed no measurable impacts. Swainsonine concentrations were 16–20 times higher in E+ plants (122.6–151.7 mg/kg) than in E− plants. Geospatial analysis revealed that poisoning hotspots for herbivores consistently occurred in regions with extreme winter conditions (minimum temperatures ≤ −17 °C and precipitation ≤ 1 mm during the driest month), suggesting context-dependent benefits under abiotic stress. These findings suggest that the ecological role of A. oxytropis may vary depending on both host species and environmental context, highlighting a trade-off between growth costs and potential stress tolerance conferred by A. oxytropis. The study underscores the need for field validation to elucidate the adaptive mechanisms maintaining this symbiosis in harsh environments.